RELATIONSHIP BETWEEN PARENTING STYLES, TEMPERAMENT AND SOCIAL ADJUSTMENT IN CHILDHOOD: A REVIEW - Ato Lozano, Ester; Galián Conesa, María Dolores; Huéscar Hernández, Elisa (Anales de Psicología / Annals of Psychology, 2007)
The objective of this work is to review theorically the main variables that are affecting child social development. Tradicionally, social adjustment study has relied upon unidirectional influence that the parents have as socialization agents. However, this position has generated several criticisms about its severe inflexibility, because other variables seem to participate in adjustment outcomes, such as temperament. Main effects models have considered the independent contributions of parenting and temperament on posterior social adjustment, but these models are consid-ered insufficient to explain the complex relationship between these variables. For this reason, interactive models have been considered the opti-mal ones to explain the association between parenting, temperament and adjustment. From the perspective of interactive models it has been con-cluded that parenting is taking part in social adjustment in a different way depending on temperamental characteristics showed by the infant.